Analisis Muhassinatul Ma’mawiyah pada Syair Abbas Bin Ahnaf: Hati Perempuan Adalah Batu - Batu - Nursukma Suri; Arif Rahman Harefa; Fitriah Pujaan; Rijalul Faizul Ichsan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the elements of al-muhassinat al-ma‘nawiyyah in the poem Qulubu al-Nisa’ Sukhur by Abbas Ibn al-Ahnaf and to examine how these rhetorical devices strengthen emotional expression and enrich meaning. The research addresses how semantic embellishments are employed in classical Arabic love poetry to convey complex emotional messages. This study uses a qualitative library research approach, collecting and reviewing relevant books, journal articles, and scholarly works. The data were analyzed using descriptive content analysis focusing on the poetic text. The findings reveal that the poem contains various elements of al-muhassinat al-ma‘nawiyyah, including tauriyah, thibaq, muqābalah, husnu ta‘līl, ta’kīd al-madh bimā yusyabbihu al-dzamm, and ta’kīd al-dzamm bimā yusyabbihu al-madh. These rhetorical features function not merely as ornamental devices but as meaningful strategies that intensify emotional depth related to love, longing, and suffering. The study concludes that the poem reflects the richness of classical Arabic rhetoric in constructing layered, symbolic, and communicative meanings.